ANRIL and atherosclerosis. (8th November 2019) - Chen, Li; Qu, Hua; Guo, Ming; Zhang, Ying; Cui, Yuanyuan; Yang, Qiaoning; Bai, Ruina; Shi, Dazhuo
Abstract: What is known and objective: The 3.8‐kb‐long antisense non‐coding RNA at the INK4 locus (ANRIL) is transcribed from the short arm of human chromosome 9 on P21 and is associated with malfunction of the vascular endothelium, vascular smooth muscle cell (VSMC) proliferation/migration/senescence/apoptosis, mononuclear cell adhesion and proliferation, glycolipid metabolism disorder and DNA damage. Hence, ANRIL plays an important role in atherogenesis. Moreover, genome‐wide association studies (GWAS) have identified ANRIL as a biomarker that is closely related to coronary heart disease (CHD). The objective of this review was to discuss the pathological mechanism of ANRIL in atherosclerotic development and its significance as a predictor of cardiovascular disease. Methods: Review of the PubMed, EMBASE and Cochrane databases for articles demonstrating the roles of ANRIL in the development of atherosclerotic diseases. Results and discussion: The abnormal expression of ANRIL is linked to vascular endothelium injury; the proliferation, migration, senescence and apoptosis of VSMCs; mononuclear cell adhesion and proliferation; glycolipid metabolism disorder; DNA damage; and competing endogenous RNAs. Moreover, ANRIL accelerates the progression of CHD by regulating its single nucleotide polymorphisms (SNPs). What is new and conclusion: Considering that ANRIL accelerates atherosclerosis (AS) development and is a risk factor for CHD, it is reasonable for us to explore an efficacious ANRIL‐based therapy for AS in CHD. Abstract : The abnormal expression of ANRIL promotes the development of atherosclerosis and ANRIL is novel biomarker closely associted with coronary heart disease.